Implementasi Keadilan Restoratif sebagai Penyelesaian Tindak Pidana Anak pada Wilayah Kerja Balai Pemasyarakatan Kelas II Polewali - Aldis Ruly Subardi (CV Rewang Rencang, 2025)
Children as the nation's next generation are influenced by various factors in their growth and development, including the environment which can cause legal conflicts. Law No. 11 of 2012 provides the basis for handling children in conflict with the law (ABH) through a restorative justice approach. This approach resolves problems by involving all relevant parties for recovery, not revenge. Diversion, as part of restorative justice, transfers settlements outside of court to reduce negative impacts on children. However, understanding of diversion remains limited among the families of both perpetrators and victims, making the role of law enforcement officers (LEOs), particularly in the Polewali area of West Sulawesi, crucial to achieving this goal.